Features ontogenesis of Aconitum talassicum M.Pop. and its role in the plant cover in nature reserve Aksu- Dzhabagly (Experimental biology, 2015)
Morphological characteristics of Aconitum talassicum M. Pop., listed in the Red Book of Kazakhstan based on observations of 1969-1971 and 2001-2003. are contained in the article. The main stages of ontogeny, especially phenology, the data on seed and feed efficiency are described in this article
Keywords: morpholog; cenopopulation; association; generative shoot; seed productivity; ontogeny; raw material productivity